Dermatological Conditions Associated with Pregnancy: A Hospital Based Study - Pandey, Sumit; Sharma, Nirmala; Pokhrel, Kumar (Journal of Nepalgunj Medical College, 2019)
Background: Pregnancy Changes can be both physiologic and pathologic, affecting commonly the skin, nails, and hair shafts. Pregnancy has immunologic, endocrine, metabolic and vascular changes, which leads to changes of skin and its appendages and can affect every organ of pregnant women including the skin. Pregnancy also modifies the course of a number of preexisting dermatological conditions. The aim of our study was to study the common skin manifestation Objectives: during pregnancy. Material and Method: Hundred pregnant women were enrolled in the study. This is a hospital- based prospective cross- sectional descriptive study, conducted in the out-patient department (OPD) of Department of Dermatology and Venereology and Department and Obstetrics and Gynecology at Nepalgunj Medical College Teaching Hospital Kohalpur, Banke Nepal, conducted over a period of two year, June 2016 to May 2018. A detailed history along with complete cutaneous examination was carried out in all patients. Relevant investigations were done wherever necessary. Result: A total of 100 pregnant women were recruited in our study from June2016 to May 2018. Out of these, 65(65%) were primigravidas and 35(35%) were multi gravidas. Their age range was 18 to 37 years with the mean of 24. Most of them presented in the third trimester. Pruritus was the commonest symptom accounting for 28(28%)cases. Physiological changes were seen in 75(75%) cases and 10 (10%) cases of specific dermatoses of pregnancy were seen. Conclusion: Skin manifestations are quite common in pregnancy and physiological changes were frequently seen. This study emphasizes the need for a scrupulous and meticulous search for dermatological and sexually transmitted diseases instead of a casual cursory examination and clinicians need to distinguish between physiological skin changes and specific dermatoses of pregnancy for better patient care.